Microplastic particles reduce reproduction in the terrestrial worm Enchytraeus crypticus in a soil exposure. (December 2019) - Lahive, Elma; Walton, Alexander; Horton, Alice A.; Spurgeon, David J.; Svendsen, Claus
Abstract: Terrestrial environments are subject to extensive pollution by plastics and, based on the slow degradation of plastics, are likely to act as long term sinks for microplastic debris. Currently the hazards of microplastics in soil and the potential impacts on soil organisms is poorly understood. Particularly the role of particle characteristics, such a size or polymer type, in dose-response relationships for microplastics is not known. The aim of this study was to assess the ingestion and toxicity of nylon (polyamide) particles, in three different size ranges, to Enchytraeus crypticus in a soil exposure. Effects were also compared with those of polyvinyl chloride (PVC) particles, in a single size range. Nylon particle ingestion was confirmed using fluorescence microscopy, with greatest ingestion for particles in the smallest size range (13–18 μm). To investigate how particle size affected survival and reproduction, E. crypticus were exposed to nylon particles in two well-defined size ranges (13–18 and 90–150 μm) and concentrations of 20, 50, 90 and 120 g/kg (2–12% w/w). An intermediate nylon size range (63–90 μm) and a larger sized PVC particle (106–150 μm), both at 90 g/kg, were also tested. Survival was not affected by either of the polymer types or sizes. Reproduction was significantly reduced, in a dose-dependent manner, by the nylon particles at high exposure concentrations (>90 g/kg). Smaller size ranges (13–18 μm) had a greater effect compared to larger size ranges (>63 μm), with a calculated EC50 for the 13–18 μm size range of 108 ± 8.5 g/kg. This greater hazard could be qualitatively linked with the ingestion of a greater number of smaller particles. This study highlights the potential for toxic effects of plastics in small size ranges to soil organisms at high exposure concentrations, providing understanding of the hazards microplastics may pose in the terrestrial environment. Graphical abstract: Image 1 Highlights: Enchytraeid survival was not affected by exposure to nylon or PVC microplastics. Enchytraeid reproduction was reduced by smaller-sized nylon microplastics. Enchytaeids ingested more particles in the smaller size ranges (13–18 μm). Nylon reduced reproduction significantly more compared to PVC. Abstract : High concentrations (∼10% w/w) of microplastics did not affect survival but did reduce reproduction in Enchytraeus crypticus, particularly in the smaller size range (13–18 μm).